PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS V SD NEGERI 161 PEKANBARU - Helda Try Meiroza; Guslinda Guslinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research was motivated by the low narrative essay writing skills of class V SD Negeri 161 Pekanbaru. This is because there are teachers who do not use the learning model, students are asked to do the writing exercises directly without being explained first. Therefore, implementing the learning model think talk write is a learning model that is suitable for use. This study aims to determine the differences in narrative essay writing skills of class V SD Negeri 161 Pekanbaru between (pretest) and (posttest) by applying the think talk write learning model. The research design used in this study was pre-experiment, the design of this study was one group pretest-posttest design. This research was conducted in class VC SD Negeri 161 Pekanbaru with 30 students consisting of 18 female students and 12 male students. Based on the results of the study it was obtained that students' narrative essay writing skills after being given treatment by applying the think talk write learning model were better and higher than those who were not treated by applying the think talk write learning model. The results showed that the average score of narrative essay writing skills before the treatment pretest was 57.07 and increased to 77.74 after being treated posttest, as well as an average gain of 0.50 which included moderate interpretation. Hypothesis test results using the t-test that thitung= 10.589 dan ttabel= 2.0452, the concluded thitung > ttabel, then Hois rejected, which means there are differences in narrative essay writing skills of class V SD Negeri 161 Pekanbaru that are significant between pretest and posttest by applying learning model think talk write.